Perceived breast milk insufficiency: Prevalence and associated factors among women attending a young child clinic in Uganda - Hindu Namyalo; Joyce Nankumbi; Tom Dennis Ngabirano (Elsevier, 2023)
Background: The most cited reason for early cessation or reduced exclusivity of breastfeeding is perceived breastmilk insufficiency. However, minimal work has been reported on perceived breast milk insufficiency, especially in Africa, where the practice of EBF remains low, hence the need to conduct the study. Objective: This study aimed at identifying the prevalence and factors associated with perceived breast milk insufficiency. Methods: This cross-sectional study was conducted among 180 mother-baby dyads with infants less than six months of age. The mothers attended an infant and young child clinic (IYCC) at an urban facility in Kampala. Data were collected using a structured interviewer-administered questionnaire using a systematic sampling procedure. Descriptive statistics and logistic regression were the major analysis techniques. Results: The prevalence of perceived breast milk insufficiency was (26 %). The reported indicators for PMI were; infant not gaining enough weight (38 %) and infant crying even after breastfeeding (38 %). Mothers who were unmarried (aOR = 0.18; 95 % CI = 0.05-0.61), and mothers who consumed less than two liters of fluid daily (aOR = 0.045; 95 % CI = 0.005-0.37) were more likely to experience perceived breast milk insufficiency. There is a need for continued reassurance and professional support for women to breastfeed their babies successfully.